Bicine promotes rapid formation of beta-sheet-rich amyloid-beta fibrils - Kim, Hye Yun; Lee, HeeYang; Lee, Jong Kook; Kim, Hyunjin Vincent; Kim, Key-Sun; Kim, YoungSoo (PUBLIC LIBRARY SCIENCE, 2020)
Fibrillar aggregates of amyloid-beta (A beta) are the main component of plaques lining the cerebrovasculature in cerebral amyloid angiopathy. As the predominant A beta isoform in vascular deposits, A beta(40) is a valuable target in cerebral amyloid angiopathy research. However, the slow process of A beta(40) aggregationin vitrois a bottleneck in the search for A beta-targeting molecules. In this study, we sought a method to accelerate the aggregation of A beta(40) in vitro, to improve experimental screening procedures. We evaluated the aggregating ability of bicine, a biological buffer, using various in vitro methods. Our data suggest that bicine promotes the aggregation of A beta(40) with high speed and reproducibility, yielding a mixture of aggregates with significant beta-sheet-rich fibril formation and toxicity.